Pendaftaran Tanah Sporadik dengan Alat Bukti Tertulis Hak Lama ( Hak Adat ) dalam Peraturan Pemrintah Nomor 18 Tahun 2021 ( Sosialisasi Abdimas di Desa Tonggara Kedungbanteng Kabupaten Tegal) - Evy Indriasari; Moh.Taufik; Siswanto Siswanto; Fajar Ari Sudewo; Imawan Sugiarto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Land registration is the only way to maintain land controlled by both individuals and legal entities. Land registration will provide legal certainty for land rights holders. Land rights in Law Number 5 of 1960, concerning Basic Agrarian Principles, including Ownership Rights, Building Use Rights, Cultivation Use Rights, Usage Rights. The Faculty of Law, Pancasakti University, Tegal, felt called to meet with the community and discuss Government Regulation Number: 18 of 2021, concerning Management Rights, Land Rights, apartment units and Land Registration. The purpose of implementing this Community Service is of course to educate the public that the news on social media is not true, there is still room or provisions in Government Regulation Number: 18 of 2021, for old rights to be registered, but with the concept of Recognition of Rights.